Protective effects and mechanism of curcumin in animal models of pulmonary fibrosis: a preclinical systematic review and meta-analysis - Hanyu, Fang; Zheng, Hong; Jiaqi, Wang; Tairan, Dong; Yiyuanzi, Zhao; Qiwen, Yang; Ying, Liu; Hongchun, Zhang; Lu, Liu (Frontiers in Pharmacology, 2023)
Introduction: At present, there is a lack of effective treatment for pulmonary fibrosis (PF), and a number of studies have confirmed that curcumin (CUR) has a good effect on PF.qusetion: Is CUR effective in preclinical trials for PF and what is its mechanism of action? Methods: Animal reports of PF treated with CUR were searched from Pubmed, Embase, Web of Science and Cochrane Library from January 1, 2000 to April 19, 2023 to compare CUR treatment of PF with a no-intervention model group. A previous registration (nsply registration number: INPLASY202360084) of this review protocol was undertaken.Results：The meta-analysis included 27 publications and 29 studies involving 396 animals.CUR significantly improved the degree of fibrosis, levels of inflammation, and oxidative imbalances in lung tissue in animal models of PF. In terms fibrosis, such as HYP content (SMD = -4.96; 95% CI = -6.05 to -3.87;p = 0.000).In terms of inflammatory indicators, such as MPO activity (SMD = -2.12; 95% CI = -4.93 to 0.69; p = 0.000).In terms of oxidation index, such as MDA(SMD = -5.63; 95% CI = -9.66 to -1.6; p = 0.000).CUR significantly improved the degree of fibrosis, levels of inflammation, and oxidative imbalances in lung tissue in animal models of PF. Due to the quantitative and qualitative limitations of current research, more high-quality studies are needed to verify the above conclusions.